(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2023)
The miniaturisation of electrical tomography sensors such as EIT has become popular recently and these miniaturised sensors were investigated for 2D and 3D imaging of cells in EIT. Nevertheless, research on miniaturisation of ECT sensor also existed which were based on peripheral electrode sensor which had electrodes arranged on the surface around the sensing chamber. However, the study on the miniature peripheral ECT sensor was limited to 2D image reconstruction and detection of presents of samples in the sensing chamber only and lacked the works on the 3D imaging capability. Therefore, this article investigates the 3D image reconstruction capability of peripheral on-chip ECT sensor through simulation approach by simulating a cube phantom at several test positions in the sensing chamber. Eventually, the 3D and 2D images were reconstructed and the 3D imaging capability of the sensor was characterised qualitatively based on visual inspection of the reconstructed image. The simulation results revealed that the 3D imaging capability of peripheral on-chip ECT sensor was limited to the region where electrodes were present only. However, the 2D reconstructed image results showed that the sensor was able to locate the positions of test phantom in the sensing chamber accurately.